Estudo analítico da convecção natural junto a uma placa inclinada para números de Prandtl baixos - Lourenço, Hamilton (1971)
The present work performs a perturbation analysis of laminar free convection about an inclined isothermal plate, using the classical boundary layer solution as the zeroth-order perturbation. The analysis is extended to second-order perturbations and the effects of the additional terms considered in the conservation equations are investigated separately. The perturbation equations were solved Prandtl numbers 0.733 and 0.03 and inclination angles and 60. Velocity and temperature profiles are compared to numerically for of the experimental results existing in the literature. Nusselt number versus Grashof number curves are plotted. Limiting Grashof numbers corresponding to heat flux corrections of 5 percent are presented.